Akkermansia muciniphila Improves Host Defense Against Influenza Virus Infection - Hu, Xiaotong; Zhao, Ya; Yang, Yong; Gong, Wenxiao; Sun, Xiaomei; Yang, Li; Zhang, Qiang; Jin, Meilin (Frontiers in Microbiology, 2021)
Infection with the influenza virus can alter the composition of gut microbiota while its pathogenicity can, in turn, be highly influenced by gut microbiota. However, many details remain to be determined. H7N9 influenza virus is an emerging zoonotic pathogen which has caused 616 people deaths and created huge losses in the poultry industry. Here, we investigated the effects of highly pathogenic H7N9 infection on gut microbiota and analyzed potential anti-influenza microbes. The 16S sequencing results show that H7N9 infection causes alteration in the gut microbiota in mice, including the upregulation of Akkermansia, Ruminococcus 1, and Ruminococcaceae UCG-010 and the downregulation of the Rikenellaceae RC9 gut group and Lachnoclostridium. Although the abundance of Akkermansia muciniphila is positively related to H7N9 infection, the oral administration of cultures, especially of pasteurized A. muciniphila, could significantly reduce the weight loss and mortality caused by H7N9 infection in mice. Furthermore, we found that the oral administration of pasteurized A. muciniphila could significantly downregulate the pulmonary virus titers and IL-1β and IL-6 of H7N9 infected mice but upregulate IFN-β, IFN-γ, and IL-10, suggesting that the anti-influenza role of A. muciniphila could be due to its anti-inflammatory and immunoregulatory properties. Taken together, we show the change characteristics of gut microbiota associated with H7N9 infection and demonstrate the anti-influenza role of A. muciniphila, enriching knowledge about how the gut microbiota protects against influenza infection.